Immune status in patients differing in the stage of choroidal melanoma - D.A. Drumi (Journal of Ophthalmology)
Purpose: To perform a pre-treatment comparison of patients with different stages of choroidal melanoma (CM) for humoral and cell-mediated immune status. Material and Methods: This immune status study included 35 patients with T1 CM (group 1) and 31 patients with T1 to T3 CM (group 2) who were treated at the State Institution “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine”. These patients were compared with 44 practically healthy individuals (group 3 or controls) for immune status. Immunologic evaluation of peripheral blood included absolute counts and percentages of leukocytes, lymphocytes, CD3+ T cells, CD4+ T helpers, CD8+ T suppressors, CD19+ B cells, СD16+ natural killer (NK) cells, phagocytic neutrophil activity (PNA), and imminoglobulins (Ig) A, M and G. Results: Pre-treated patients in groups 1 and 2 had significantly increased absolute counts of leukocytes (p1-3 = 0.005 and p2-3 = 0.0003, respectively), lymphocytes (p1-3 = 0.04 and p2-3 = 0.0002, respectively), and cytotoxic CD8+ T suppressors (p1-3 = 0.0002 and p2-3 = 0.001, respectively), and CD4+/CD8+ ratio (p1-3 = 0.00002 and p2-3 = 0.0000, respectively), and PNA (p1-3 = 0.0004 and p2-3 = 0.0001, respectively), IgA (p1-3 = 0.003 and p2-3 = 0.009, respectively), and IgM (p1-3 = 0.0007 and p2-3 = 0.0000, respectively). There was, however, no significant difference in other parameters between patients and controls. Compared to patients in group 1 and controls, patients in group 2 had significantly increased absolute counts of CD4+ T helpers (p1-2 = 0.02 and p2-3 = 0.0000, respectively), СD16+ NK cells (p1-2 = 0.03 and p2-3 = 0.003, respectively), and IgM levels (p1-2 = 0.02 and p2-3 = 0.0000, respectively), and significantly decreased IgG levels (p1-2 = 0.006 and p2-3 = 0.003, respectively). Conclusion: In pre-treatment patients differing in the stage of CM, the tumor process responds to immune changes that are expressed by activation of humoral and cell-mediated immunity (an increase in the activity of CD3+ T cells, CD4+ T-helpers, CD8+ T-suppressors, CD16+ NK cells, and IgM and IgA levels), which may have a substantial impact on treatment effect.